Therapy of chronic extensor mechanism deficiency after total knee arthroplasty using a monofilament polypropylene mesh - Fuchs, M; Gwinner, C; Meißner, N; Pfitzner, T; Perka, C.; von Roth, P. (Frontiers in Surgery, 2022)
Lesions of the quadriceps or patellar tendon after total knee arthroplasty (TKA) are a rare but serious complication which, if left untreated, can lead to loss of function of the knee joint. While acute and subacute extensor mechanism disruptions may have several causes, chronic deficiencies are often related to multiple prior revision surgeries for joint infection or aseptic TKA failure. Up to date, biological allograft reconstruction showed unsatisfying results. The use of a monofilament polypropylene mesh is a promising approach for this pathological condition. The aim of the present study was to evaluate clinical, functional and patient reported outcomes of this procedure in patients with chronic extensor mechanism deficiency. Twenty-eight patients with chronic extensor mechanism deficiency (quadriceps tendon rupture n=9, patellar tendon rupture n=19) after TKA were included in this retrospective study. None of the patients were lost to follow-up. Surgical reconstruction was performed at one institution between 2014 and 2020 with a monofilament polypropylene mesh (Marlex Mesh, Bard, Murray Hill, USA). The mean age at the time of surgery was 69 years. Patients presented with a mean BMI of 33 kg/m2. The mean follow-up period was 23 months. The 2-year survivorship free of mesh revision was 89% (95% confidence interval [CI]: 75% to 100%). Three patients (11%) had to undergo revision because of mechanical mesh failure and received another polypropylene mesh. No further revisions were performed thereafter. Flexion was 87° (range, 30-120°) on average. The majority of patients (75%, 21/28) had a full active extension. The mean active extension lag after surgery was 4 degrees (range, 0-30°). We observed a substantial improvement of extensor mechanism function. The majority of patients had full extension and showed good clinical results. A failure rate of over 50% has been published for alternative procedures. Thus, the use of the described augmentation technique represents a reasonable treatment option for chronic extensor mechanism disruptions of the patellar tendon as well as the quadriceps tendon after total knee arthroplasty. However, there might be a potentially higher risk for infection persistence in periprosthetic joint infection cases due to the presence of a foreign material.